The world of Rembrandt, 1606-1669 - Wallace, Robert 1919- (Time-Life library of art, 1969)
Lavishly illustrated account of the life, career, works and times of the 17th century Dutch artist Rembrandt van Rijn, with background information on other artists of that period.